Agent Q, or the smell of danger! - Anderson, M. T.; Cyrus, Kurt (New York : Beach Lane Books, 2010)
As Lily, Katie, and Jasper try to return home after their adventures in Delaware, they face a protoplasmic monster, sleeping gas, a runaway rice cart, sentient lobsters, and spies of the Awful and Adorable Autarch of Dagsboro.
010-up.
Keywords: Spy stories; Adventure stories; Adventure and adventurers -- Fiction; Spies -- Fiction; Humorous stories; Mystery and detective stories